A method for investigating population declines of migratory birds using stable isotopes: origins of harvested lesser scaup in North America. - Keith A Hobson; Michael B Wunder; Steven L Van Wilgenburg; Robert G Clark; Leonard I Wassenaar (PLoS ONE, 2009)
Elucidating geographic locations from where migratory birds are recruited into adult breeding populations is a fundamental but largely elusive goal in conservation biology. This is especially true for species that breed in remote northern areas where field-based demographic assessments are logistically challenging.Here we used hydrogen isotopes (deltaD) to determine natal origins of migrating hatch-year lesser scaup (Aythya affinis) harvested by hunters in the United States from all North American flyways during the hunting seasons of 1999-2000 (n = 412) and 2000-2001 (n = 455). We combined geospatial, observational, and analytical data sources, including known scaup breeding range, deltaD values of feathers from juveniles at natal sites, models of deltaD for growing-season precipitation, and scaup band-recovery data to generate probabilistic natal origin landscapes for individual scaup. We then used Monte Carlo integration to model assignment uncertainty from among individual deltaD variance estimates from birds of known molt origin and also from band-return data summarized at the flyway level. We compared the distribution of scaup natal origin with the distribution of breeding population counts obtained from systematic long-term surveys.Our analysis revealed that the proportion of young scaup produced in the northern (above 60 degrees N) versus the southern boreal and Prairie-Parkland region was inversely related to the proportions of breeding adults using these regions, suggesting that despite having a higher relative abundance of breeding adults, the northern boreal region was less productive for scaup recruitment into the harvest than more southern biomes. Our approach for evaluating population declines of migratory birds (particularly game birds) synthesizes all available distributional data and exploits the advantages of intrinsic isotopic markers that link individuals to geography.